Y-chromosome STR haplotypes in two population samples: Azores Islands and Central Portugal - Carvalho, Mónica (2003)
The Y-chromosome haplotypes defined by nine STRs (DYS19, DYS385, DYS389I, DYS389II, DYS390, DYS391, DYS392 and DYS393) were studied in 207 unrelated individuals from Central Portugal and 63 from Azores Islands. The most common haplotype in Central Portugal was shared by 3.4% of the males, while 160 haplotypes were unique. In Azores Islands the most common haplotype was shared by 6.4% of the males, while 40 haplotypes were unique. The values of haplotype diversity were 0.993 for Central Portugal and 0.976 for Azores Islands.